Analisis Kualitas PMPV-IG Berbahasa Ibu untuk Menggali Kemampuan Pemecahan Masalah Siswa pada Konsep Gerak Parabola - Ranimah; Alvionita Silvianty; Lia Wahyuningsih Budiarti (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
The purpose of this study was to examine the quality of the Projectile Motion Problem Video–Interview Guide (PMPV-IG) developed in the mother tongue, focusing on aspects of validity and reliability. The PMPV-IG was designed to explore students’ problem-solving abilities in the concept of projectile motion within sports-related activities. Fifteen eleventh-grade students whose mother tongue is the Ketapang Malay Dialect (BMDK) were selected using a purposive sampling technique. The PMPV-IG was constructed based on the five problem-solving stages proposed by Heller’s theory: visualizing the problem, describing the problem in terms of physics, planning a solution, executing the problem-solving plan, and evaluating the solution. Its validity covered three aspects: content validity of the use of the Ketapang Malay Dialect, content validity regarding the alignment between indicators and essential questions, and construct validity. The construct validity was assessed using Aiken’s V formula, while the reliability of the PMPV-IG items was measured using Cronbach’s Alpha formula. The evaluation was conducted by two language experts and three physics experts. The findings indicate that the PMPV-IG achieved a very high level of validity, with an average score of 0.875, and demonstrated high reliability with an alpha value of 0.81. Therefore, the PMPV-IG is deemed valid and reliable, making it suitable for exploring students’ problem-solving abilities in the concept of projectile motion.